De koorbanken in de Martinikerk te Bolsward en hun Europese context - Steensma, Regnerus (2012)
The choir stalls in the Martinikerk in Bolsward miraculously escaped the iconoclasm. They now constitute the greatest treasure of medieval sculpture in Friesland. They were made around 1490 and have carvings with a wide variety of representations. These include biblical stories, lives of saints, as well as scenes of everyday life and ornamental work. The carving of the pew from the Broerekerk shows influence from Brabant, that of the pews from the Martinikerk influence from northern Germany.Many fine photographs show not only the wealth of Bolsward but also the choir stalls elsewhere in the Netherlands and in Germany.Dr Regnerus Steensma was senior lecturer at the University of Groningen in Architecture and Iconography of Christianity and director of the Institute for Liturgical Studies until 2002. He published books and articles on church building and church design, especially in the northern part of the Netherlands. In addition, he is a church photographer.
Keywords: Religion; Iconography; Fine art; Bolsward (Netherlands)